Combination of Words as a Syntax Unit in Linguistics Research - Isroilova Odinahon G’anijonovna (Research Parks Publishers, 2021)
In this article, the system as a syntactic level unit for a phrase from a linguistic point of view, this syntactic unit is formal and semantic emphasis will be placed on highlighting the features. The invaders tried to assimilate their language into the local people by force and burned manuscripts written in the local language. The Uzbek people have gone through such moments, but they bravely overcame such difficulties and trials with their intelligence, will and high spirituality.